Probiotics as Support for Antibiotic Therapy: Benefits and Risks - Kinga Dominiczak; Katarzyna Szafrańska; Aleksandra Mucha; Ewa Chodkowska; Natalia Jakubczyk; Elżbieta Leszczyńska-Knaga; Sylwia Graszka; Aleksander Szeps; Patrycja Dominiczak; Kinga Bielas (Quality in Sport)
Antibiotic therapy, while effective in combating bacterial infections, can disrupt the gut microbiota, often leading to antibiotic-associated diarrhea (AAD). In this context, probiotics have been explored as potential adjuncts to alleviate these adverse effects. Research indicates that using probiotics during antibiotic treatment may reduce the risk of AAD. For instance, a meta-analysis by Szajewska and Kołodziejczyk found that probiotics decrease the likelihood of AAD in adults, with higher doses being more effective than lower ones. However, the efficacy of probiotics in protecting the diversity of the gut microbiome during antibiotic therapy remains controversial. A systematic review and meta-analysis conducted by Matuskova et al. suggest that probiotic supplementation does not significantly prevent the reduction of gut microbiota diversity caused by antibiotics. Moreover, concerns about the safety of probiotics have been raised, particularly regarding the potential transfer of antibiotic resistance genes. A systematic review by Zhang et al. highlights the need for further research to evaluate the risks associated with the spread of antibiotic resistance through probiotic strains. Therefore, while probiotics may offer certain benefits as adjuncts to antibiotic therapy, it is essential to carefully consider the associated risks and conduct further studies to fully understand their impact on patient health.